The Relevance of the Concept of Hirabah to Organized Crime and Modern Terrorism - Hairul Anam; Ahmad Rifai Yoga; Nadilah Andini; Wenni Nahdiani Tanjung; Suci Hidayati Malau (ISNU Sumatera Utara, 2026)
This study examines the relevance of the concept of hirābah in Islamic criminal law to contemporary organized crime and terrorism. Historically, hirābah addresses acts of open violence that threaten public security, instill fear, and disrupt social order, with sanctions aimed at protecting life, property, and communal stability. Using a normative legal research method with a qualitative approach, the study analyzes classical fiqh texts, contemporary scholarship, and comparative legal frameworks to explore the elements, characteristics, and objectives of hirābah. The findings reveal substantial conceptual alignment between classical hirābah and modern forms of collective violence, as both involve deliberate acts that destabilize society and generate widespread fear. However, contemporary crimes exhibit complex ideological, transnational, and technological dimensions requiring normative adaptation. The study concludes that while hirābah provides a valuable legal and sociological framework, its application to modern criminality necessitates contextual reconstruction, integrating Islamic jurisprudence with national and international legal systems for effective prevention, deterrence, and public security.